Capabilities of fluorescent spectroscopy in diagnosis of tumors of the ent-organs - N. A. Daikhes; V. V. Vinogradov; I. A. Kim; S. S. Reshulsky; V. F. Prikuls; O. V. Karneeva; A. M. Khabazova; D. V. Prykule (Опухоли головы и шеи, 2021)
Introduction. Diagnosis verification in patients with malignant tumors developed in the context of chronic inflammation is technically complex with a high percentage of false negative results of histological examination. None of the methods provides sufficiently accurate results necessary for ruling out or confirming a diagnosis.The study objective is to test a new patented method of pre- and intraoperative differential diagnosis of oncological pathology of the ent-organs using the "InSpektr-M" hardware and software system.Materials and methods. The study included 30 patients with suspected malignant tumors of the larynx. The study excluded patients with previously verified diagnosis of malignant tumor of the larynx. A diagnostic probe emitting laser light with wavelength 350 nm and radiation power density 25 mW/cm2 was introduced through an additional channel of a fiberscope for a period of time sufficient for excitation of intrinsic tissue fluorescence (from 10-6 to 10-9 ms). Fluorescence intensity in the range of wavelengths between 600 and 650 nm was measured. This intensity was conditionally labelled "epithelial proliferative activity index". Spectrometric analysis of the intact points allowed to evaluate normal values for an individual patient; in the areas with the maximal increase in the index, targeted biopsy was performed.Results. Values obtained during examination of various types of tumors (epithelial and non-epithelial) are different while tumor location has a negligible effect. In patients with malignant tumors containing non-squamous epithelium, increased protoporphyrin IX and decreased FAD fluorescence were observed in the direction from intact tissues to the center of the suspected tumor; in patients with malignant tumors containing squamous epithelium: increased protoporphyrin IX fluorescence with maximum at 635 nm and dynamic increase in FAD fluorescence in the direction from intact tissues to the tumor center.Conclusion. Fluorescent spectroscopy can be used for pre- and intraoperative differential diagnosis of squamous and non-squamous cancers of the ENT-organs. Further studies for establishment of reference values of fluorescence intensity in intact and affected tissues are necessary.